Surface enhanced Raman optical activity as an ultra sensitive tool for ligand binding analysis. Issue 3 (2007) - Johannessen Johannessen, Christian Christian; Abdali Abdali, Salim Salim
Abstract : The Surface Enhanced Resonance Raman Scattering (SERRS) and Surface Enhanced Resonance Raman Optical Activity (SERROA) spectra of myoglobin and the myoglobin-azide complex were measured on very dilute samples (100 nM protein) in order to analyze the sensitivity of SERROA spectroscopy when inducing small structural changes. While the SERRS spectra of the two compounds were virtually identical, comparison of the SERROA spectra revealed several differences, including frequency shifts and changes in signal intensity, consistent with structural change in the porphyrin prosthetic group of the protein upon azide complexation. Application of this method allows for rapid analysis of ligand binding in metalloproteins in dilute aqueous solution and could in the future, when combined with theoretical studies, increase the obtainable structural resolution of proteins beyond that of X-ray analysis.